The awareness of money saving among secondary students at Dungun / Wan Nur Aziemah Wan Mohd Azmi - Wan Mohd Azmi, Wan Nur Aziemah (2013)
The introduction of money saving is the most important for all people especially for secondary students. They will grow up day by day so they should have the knowledge or expose about the saving to make sure that they know it. There are many advantages to them as students because the money saving not only focusing on saving at home but it is refer to saving at the bank and other types of saving. Therefore, there is a need to understand the awareness of money saving and to identify the factors that influence secondary students to save the money. The study objective is to measure the level of awareness of money saving, to determine the factors that contributes the awareness of money saving and to identify the most affecting factors contributes the awareness of secondary students in money saving. The study more focuses to the secondary students in four types of school which are normal, religious, science and technique at Dungun. Reliability test, frequency distribution, correlation coefficient test and linear regression test are use to analyze data. From the finding, attitude, parent encouragement and saving programs have significant relationship with factors influencing the awareness of money saving among secondary students. Researcher also found that the factor of attitude is the highest factors and parent encouragement has the lowest relationship with the factors influencing the awareness of money saving among secondary students.